2019
DOI: 10.1002/slct.201903197
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidative C(CO)–C Bond Cleavage under Catalyst‐Free and Additive‐Free Conditions

Abstract: It was found that C(CO)–C bonds could undergo aerobic oxidative cleavage under catalyst‐free and additive‐free conditions. In the presence of environmentally friendly reagents including O2 and H2O, a series of 1,1‐diphenylacetones, diphenyl‐acetaldehydes, phenylacetones and their derivatives were smoothly converted into the desired products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…On the other hand, the above‐mentioned methods rely on the use of various catalysts. By comparison, catalyst‐free process should be more attractive from environmental and economic perspectives [12b,c] . Thus we have attempted to actualize this goal, and found that lignin β ‐O‐4 ketone models undergo smoothly the hydrogenolysis by light‐induced water‐donating transfer hydrogenation, which provided an example of catalyst‐free hydrogenolysis of lignin β ‐O‐4 ketone models with water as an H‐transfer reagent (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the above‐mentioned methods rely on the use of various catalysts. By comparison, catalyst‐free process should be more attractive from environmental and economic perspectives [12b,c] . Thus we have attempted to actualize this goal, and found that lignin β ‐O‐4 ketone models undergo smoothly the hydrogenolysis by light‐induced water‐donating transfer hydrogenation, which provided an example of catalyst‐free hydrogenolysis of lignin β ‐O‐4 ketone models with water as an H‐transfer reagent (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although this method is still often used, it presents severe drawbacks such as the use of toxic transition metals and an excess of stoichiometric oxidants, and the generation of large amounts of by‐products To address these concerns, metal‐free methods have emerged for the direct C–C σ‐bond oxidative cleavage . The fascinating development in this direction is the metal‐free oxidative cleavage with molecular oxygen as oxidant, which include the base‐, and in situ formed enamine‐ promoted or mediated, and auto‐oxidative cleavage method . For example, Jiang reported a transition‐metal‐free aerobic oxidative C–C bond cleavage and esterification of acyclic α‐hydroxy ketones via base‐promoted strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[4b] Since the seminal work by Chi in 2012, in situ formed enamine‐mediated strategy was developed for the C–C bond oxidative cleavage of aldehydes and ketones to synthesize chiral ketones,[5a] esters,[5b] and amides,[5c], [5d] using molecular O 2 as the sole oxidant. In 2019, Ren, Lu, and co‐workers found that C(CO)–C bonds could undergo aerobic oxidative cleavage under catalyst‐free and additive‐free conditions at 120 °C . And to our best knowledge, I 2 /O 2 catalytic system promoted unstrained C–C single bond cleavages is quite rare (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“… 5 The diarylacetaldehydes are known to undergo decarbonylation, resulting in the corresponding benzophenones under oxidative and halogenation conditions. 6 The possibility of combining all these events, i.e , olefin oxidation, pinacol rearrangement, and/or oxidative decarbonylation, is interesting, and this has been executed very recently for the direct synthesis of carbonyl compounds from the styrenes/stilbenes ( Figure 1 ). 7 …”
Section: Introductionmentioning
confidence: 99%